A critical analysis of Turkey's search for decreasing energy dependency under AKP governments - Özyılmaz, Batuhan Hüseyin (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
AKP hükümetleri döneminde Türkiye'nin enerji bağımlılığını düşürme arayışlarının eleştirel analizi